Second records and redescriptions of two rare thecate hydroids (Cnidaria: Hydrozoa) from the southwestern Pacific - Galea, Horia R. (Zootaxa, 2021)
Two thecate hydroids, Carpocladus fertilis Vervoort & Watson, 2003 (family Aglaopheniidae Marktanner-Turneretscher, 1890) and Gonaxia constricta (Totton, 1930) (family Gonaxiidae Maggioni, in Galea & Maggioni, 2021), are recorded for the first time from off New Caledonia, thus outside their original area of distribution in New Zealand waters. Specimens of both sexes of C. fertilis occur in the present collection, allowing the first description of its so far unknown female gonothecae. The trophosome of G. constricta, the only known to date, is thoroughly redescribed, pending the discovery of its gonothecae.